The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1037/1076-898x.10.3.156
|View full text |Cite
|
Sign up to set email alerts
|

Confidence-Accuracy Calibration in Absolute and Relative Face Recognition Judgments.

Abstract: Confidence-accuracy (CA) calibration was examined for absolute and relative face recognition judgments as well as for recognition judgments from groups of stimuli presented simultaneously or sequentially (i.e., simultaneous or sequential mini-lineups). When the effect of difficulty was controlled, absolute and relative judgments produced negligibly different CA calibration, whereas no significant difference was observed for simultaneous and sequential mini-lineups. Further, the effect of difficulty on CA calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
121
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(160 citation statements)
references
References 25 publications
(57 reference statements)
30
121
5
Order By: Relevance
“…The calibration functions reveal, in all conditions, a generally linear, positive relationship between the level of confidence expressed and the probability that a face had been seen before. For typical faces, this relationship is most evident in the upper half of the confidence scale (consistent with previous research demonstrating that individuals are better at discriminating degrees of "oldness" than degrees of "newness"; e.g., Weber & Brewer, 2004).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The calibration functions reveal, in all conditions, a generally linear, positive relationship between the level of confidence expressed and the probability that a face had been seen before. For typical faces, this relationship is most evident in the upper half of the confidence scale (consistent with previous research demonstrating that individuals are better at discriminating degrees of "oldness" than degrees of "newness"; e.g., Weber & Brewer, 2004).…”
Section: Resultssupporting
confidence: 70%
“…First, if ecphoric confidence ratings are insensitive to memory quality, they will not provide a reliable index of ecphory/recognition. Studies examining retrospective confidence ratings have consistently demonstrated that retrospective confidence judgments are less sensitive than memory performance itself to a variety of manipulations (e.g., Gigerenzer, Hoffrage, & Kleinbölting, 1991;Weber & Brewer, 2004). Although retrospective and ecphoric confidence are distinct, both presumably index memory and stimulus discriminability (see Macmillan & Creelman, 1991;Van Zandt, 2000;Wixted & Mickes, 2010).…”
mentioning
confidence: 99%
“…A common example of this line of research in psychologylaw is accuracy of eyewitness testimony. Researchers demonstrated that confidence in one's identification of a defendant does not necessarily imply high accuracy (e.g., Weber & Brewer, 2004;Wells, Ferguson, & Lindsay, 1981). Germane to this discussion is that confidence functions as a degree of certainty about both one's judgment, and, in turn, the outcome of the testimony.…”
Section: Witness Self-efficacy and Confidencementioning
confidence: 95%
“…Each photograph was presented for 500 ms with a 500-ms interval between stimuli. An interval of 500 ms was selected to prevent floor and ceiling effects (Weber & Brewer, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Second, we used a face recognition mini-lineup task (cf. Weber & Brewer, 2004), which presents identical faces at encoding and test, albeit in a lineup. Again, this permits large-scale data collection within and between subjects.…”
mentioning
confidence: 99%